Penerapan Metode Struktur Tiga Babak dalam Penulisan Naskah Film Dokumenter “Tanah dan Waktu” - Kinanti Sasi Kirana; Kokom Komariah; Andri Yanto (Lembaga Pengembangan Kinerja Dosen, 2025)
The three-act structure is applied in the scriptwriting of the documentary film Tanah dan Waktu. This audiovisual work explores the issue of the existence of ceramic art in the current era. The purpose of its creation is to explain the application of the three-act structure in documentary scriptwriting: Act I (Set Up), Act II (Confrontation), and Act III (Resolution). The creation process includes Pre-Production, Production, and Post-Production stages, with a main focus on scriptwriting as it plays a crucial role in building a structured narrative through storyline development, interview design, and maintaining story continuity. The results show that Act I introduces the history of ceramic art and the initial perspectives of the interviewees, aiming to build basic understanding for the audience. Act II presents a deeper exploration of the issue through the views of artists and academics, highlighting the challenges of sustaining ceramic art today. Act III offers resolutions in the form of proposed solutions and hopes from the interviewees. In conclusion, applying the three-act structure helps build a strong narrative, effectively delivering the message about the current challenges faced by ceramic art.